Café das Ciências Sociais - Joinhas, Carmem Cristina de Toledo Arruda [UNESP]; Machado, Marilia Gabriella Borges [UNESP]; Mansano, Silvana [UNESP]; Poker, José Geraldo Alberto Bertoncini [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Café of Social Sciences is an extension project carried out since 2009 by the group of Social Sciences of the Tutorial Education Program (PET), whose characteristic is to promote events in places easily accessible to the population of the city of Marilia, in there is debate on matters of academic and educational interest, or who are mobilizing public opinion in some way. The topics to be addressed are set by opinion poll, conducted in high schools and places of great flow of people. After defining the topics to be discussed are identified and invited experts, preferably coming from the university, which is tasked to lecture the participants for some time, and then to make available to the public to answer questions and other requests.

O Café das Ciências Sociais é um projeto de extensão realizado desde o ano de 2009 pelo grupo de Ciências Sociais do Programa de Educação Tutorial (PET), cuja característica é a de promover eventos em lugares de fácil acesso à população da cidade de Marília, em que haja debates sobre assuntos de interesse acadêmico e escolar, ou que estejam mobilizando a opinião pública de alguma forma. Os temas a serem tratados são definidos mediante pesquisa de opinião, realizada em escolas de ensino médio e lugares de grande fluxo de pessoas. Depois de definidos os temas a serem debatidos, são identificados e convidados especialistas, preferencialmente oriundos da Universidade, que tem a incumbência de palestrar aos participantes por algum tempo, e em seguida se colocarem à disposição do público para responderem perguntas e demais solicitações.
Keywords: Social Sciences; Debates; Daily problems; Ciências Sociais; Debates; Problemas cotidianos